Profiles of entrepreneurship students: implications for policy and practice. Issue 2 (5th March 2019) - Sá, Creso; Holt, Christopher
Abstract : Purpose: While much research seeks to determine the impacts of entrepreneurship education on students, far less attention has been paid to students' motivations and interests. Understanding students' perspectives is useful, particularly as governments support the expansion of campus entrepreneurship. The purpose of this paper is to develop a deeper understanding of students' reasoning in relation to pursuing entrepreneurship education. Design/methodology/approach: Specifically, the key questions driving this study were: Why do students join experiential learning entrepreneurship programs? How do they define their goals for entrepreneurship education, and what outcomes do they value? Data were collected through interviews with 38 students participating in a range of experiential entrepreneurship programs in Ontario. Findings: Four different patterns in students' reasoning and sense making emerged from the analysis. First, "venture creators" are the prototypical student entrepreneurs who are set on creating and launching a venture. Second, "experience seekers" aim at gaining practical work experience but do not see themselves as nor intend to become entrepreneurs. Third, "explorers" aim at developing familiarity with basic concepts and opportunities in entrepreneurship, as a means to consider whether this is an attractive career option. Finally, "engagers" are actively experimenting with entrepreneurship as they gauge their "fit" and potential as entrepreneurs. Originality/value: This study's findings provide an empirically grounded check on the assumptions guiding government policy for entrepreneurship education and institutional practice. Policy and institutional attention is overly focused on venture creation, even as other outcomes are commonly espoused. Recognizing different profiles of entrepreneurship students may lead to more purposefully designed programs that have different objectives, and help distinct segments of students achieve their goals.